2021
DOI: 10.1038/s41598-021-89452-5
|View full text |Cite
|
Sign up to set email alerts
|

Sustained release of usnic acid from graphene coatings ensures long term antibiofilm protection

Abstract: Protecting surfaces from bacterial colonization and biofilm development is an important challenge for the medical sector, particularly when it comes to biomedical devices and implants that spend longer periods in contact with the human body. A particularly difficult challenge is ensuring long-term protection, which is usually attempted by ensuring sustained release of antibacterial compounds loaded onto various coatings. Graphene have a considerable potential to reversibly interact water insoluble molecules, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…In a study by Pompilio et al [48], the antibiofilm activity of usnic acid and atranorin, as pure substances, was examined, and it was shown that atranorin exhibited better action compared to usnic acid. A recent study showed that novel-type formulations such as usnic acid-impregnated graphene flakes could have a more prolonged antibiofilm activity [49]. In our study, XSH, the only extract that contained atranorin, showed the weakest antibiofilm effect compared to the other two tested extracts.…”
Section: Discussionsupporting
confidence: 51%
“…In a study by Pompilio et al [48], the antibiofilm activity of usnic acid and atranorin, as pure substances, was examined, and it was shown that atranorin exhibited better action compared to usnic acid. A recent study showed that novel-type formulations such as usnic acid-impregnated graphene flakes could have a more prolonged antibiofilm activity [49]. In our study, XSH, the only extract that contained atranorin, showed the weakest antibiofilm effect compared to the other two tested extracts.…”
Section: Discussionsupporting
confidence: 51%
“…Lyu et al 68 further constructed Dex-laden hierarchical ZnO nanotube/GO nanostructures via anodic oxidation, which brought osteogenicity and synergistic bactericidal activity to pure Zn implants. Pandit et al 69 developed usnic acid (UA)-graphene coatings, steadily releasing UA to enable long-term protection of implant surfaces against colonization by S. aureus and Staphylococcus epidermidis , even after the burst release of concentrations of UA. A team 70 synthesized polydopamine/GO- d -leucine ( d -leu) films which possessed pH-responsive antibacterial properties.…”
Section: Antibacterial Effectsmentioning
confidence: 99%
“…In another study, graphene coatings have been reported as a promising contender for anti-biofilm formation to prevent infection in medical implants. When the graphene layer is loaded with usnic acid (a strong antibacterial additive), the coating provides long-term anti-biofilm protection for up to 96 h. 167 The coating is highly effective against Staphylococcus aureus and S. epidermidis , two common biofilm-forming bacteria on medical implants.…”
Section: Applications Of Graphenementioning
confidence: 99%